The Influence of COVID-19 on Antimicrobial Resistance Trends at a Secondary Care Hospital in Slovenia: An Interrupted Time Series Analysis - Samo Jeverica; Darja Barlič Maganja; Jani Dernič; Peter Golob; Alenka Stepišnik; Bojan Novak; Lea Papst; Anamarija Juriševič Dodič; Mladen Gasparini (Antibiotics)
Background/Objectives. Our study aimed to determine the development of antibiotic resistance during the peri-pandemic period in a regional secondary care hospital using an interrupted time series analysis. Methods. We analyzed data from seven years, accounting for 441,149 patient days. The incidence density of multidrug-resistant bacteria (MDR) burden and infection was reported per 1000 patient days. Results. During the COVID-19 period, a significant increase in the mean incidence density of the total MDR burden from 4.93 to 5.81 per 1000 patient days was observed (p = 0.007). On the other hand, the mean incidence density of MDR infections decreased from 1.61 to 1.29 per 1000 patient days (p = 0.019). Using the interrupted time series analysis, the same trends were observed, namely the overall increasing trend in MDR burden and the overall decreasing trend in MDR infections. This divergent trend is mainly due to similar trends in several Gram-negative MDR, namely ESBL-EC, ESBL-KP and CRE. Conclusions. Due to the increasing burden of MDR, it is necessary to strengthen AMR surveillance. In addition, strict infection prevention and control measures, and antimicrobial stewardship programs continue to be important components in the fight against resistant bacteria.